A educação científica crítica na perspectiva dos professores de ciências - Bernardo, Tassya Hemília Porto (2023)
Critical Scientific Education (CCE) aims to train individuals who have an active, critical and conscious stance in relation to the world in which they live. This approach seeks to transform society, allowing citizens to face daily challenges with justice, ethics, based on scientific knowledge and values such as critical thinking, argumentation, responsibility, autonomy and collaboration. To promote critical scientific education, teachers need to adopt a perspective focused on critical thinking, social participation and decision-making. They must reflect on their teaching practices, seeking to expand and deepen their knowledge, skills, attitudes and values, expressed through their words, examples and actions. In the research conducted with 12 basic education science teachers in São Carlos - SP, five axes were identified through discursive textual analysis. These axes address the principles, purposes and importance of critical scientific education; methodologies and approaches; problems/challenges; advances; in addition to appreciation by family members and government officials. In developing ECC, teachers approach the science-technology-society approach by encouraging the contextualization of science content, relating different knowledge in an inter and transdisciplinary way, discussing the production of knowledge and promoting a scientific culture. For teachers, curricular demands impose challenges on the development of ECC, which, in a way, hampers some teaching practices. Despite this, teachers identify advances, highlighting the possibility of teaching science with a focus on developing an active, critical and conscious stance, with decision-making skills. Study participants also reflect on the social valuing aspects of ECC attributed by family members and government officials. Teachers realize that ECC is valued differently and, in most cases, the topic is of little importance. Therefore, investing in quality scientific education is essential to building a more informed, responsible and capable society to face the complex challenges of the contemporary world.